Systematic review: opportunities and barriers to online marketing caused by the development of the Internet of Things - Nikolaev, Dmitrii (Business: Theory and Practice, 2024)
The current research aims to systematically review the impact of the Internet of Things (IoT) on online marketing, focusing on its opportunities and challenges. Using the PSALSAR methodology, this research delves deep into the literature to understand the nature of IoT influences. The analysis reveals that while IoT offers transformative potential for online marketing, it brings with it significant challenges. Among these challenges are concerns about security, consumer perceptions, and sustainability. Furthermore, there is a noticeable gap concerning the quantifiable impact of IoT on B2B online marketing effectiveness and the long-term customer perceptions of IoT-integrated products. The estimation of effects and opportunities as well as a detailed description of challenges is an important step in every technological development.